Market disequilibrium, monetary policy, and inancial markets: Insights from new tools - Jean Luc Gaffard; Mauro Napoletano (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2018)
We revisit the main building blocks of the theoretical models underlying the monetary policy consensus before the Great Recession. We highlight how the failure of these models to prevent the crisis and to provide guidance during the recession were due to the excessive confidence in the ability of markets to coordinate demand and supply, and to the neglect of the role of finance. Furthermore, we outline the main elements of an alternative approach to monetary policy that put emphasis on the processes driving coordination in markets, and on the externalities transmitted by financial inter-linkages. Many elements of this new approach are captured by new classes of models, namely, agent-based and financial network models. We discuss some insights from these models for the conduct of monetary policy, and for its interactions with fiscal and macro- prudential policies.
Keywords: E31; E32; E5; E61; E62; 330; R&D; output-inflation dynamics; new-keynesian models; disequilibrium analysis; agent-based models; fiscal-monetary policy interactions; quantitative easing policies